ESL learners’ use of learning management system features and metacognitive online reading strategies / Nor Fazlin Mohd Ramli - Mohd Ramli, Nor Fazlin (Universiti Teknologi MARA, Kedah, 2021)
The objective of this study is to investigate the use of available features in a Learning Management System (LMS) and the metacognitive online reading strategies of adult learners of an English as a Second Language (ESL) course in Universiti Teknologi MARA (UiTM), Malaysia. A survey adapted from Online Survey of Reading Strategies (OSORS) developed by Anderson (2003) was used to gather information of 157 adult learners in semesters one and two. The survey is divided into three parts: Learners’ background, learner use of available features of an LMS and learners’ metacognitive online reading strategies. The survey revealed that these adult learners usually log into the LMS during their working hours at the office. The learners mostly used global reading strategies followed by problem-solving strategies and support reading strategies. Independent t-test reveals that there is no significant difference between semester one and semester two students in using global reading strategies, problem-solving strategies and support reading strategies. Based upon the results illustrated in this study, it can be concluded that the learners have learning goals and purpose since they used mainly global reading strategies, but they do not effectively utilize online learning tools and features that are available in the LMS.